Barcoding spindles and decorating whorls: How weavers marked their property at Cerro Azul, Peru. (2nd January 2016) - Marcus, Joyce
Abstract : Spindles with painted "barcodes" provide new information on weavers at Cerro Azul (Valley of Cañete). Sets of identically barcoded spindles are often found in a specific workbasket, making it likely that each woman coded some of her personal property. At Cerro Azul, identically barcoded spindles occur in mummy bundles, workbaskets, open-air work spaces, storage bins, and a brewery. The juxtaposition of spinning, weaving, and brewing in one work space suggests Late Intermediate behavior anticipated the aklla—an Inca institution requiring "chosen women" to weave cloth and brew beer. The Inca presumably reconfigured this behavior so that it could be administered at an imperial level, rather than the level of the residential compound as at Cerro Azul (A.D. 1000–1470).